PERSEPSI MAHASISWA AKUNTANSI PERGURUAN TINGGI SWASTA (PTS) MAKASSAR MENGENAI HUBUNGAN ANTARA PENGALAMAN DENGAN KINERJA PEMERIKSAAN PAJAK PADA KPP PRATAMA MAKASSAR - Rosmawati Rosmawati; Muhammad Nur (Universitas Muhammadiyah Makassar, 2020)
This study has a specific purpose to be obtained to determine the perception of PTS accounting students about the relationship between experience and motivation to check with tax audits at Makassar Primary Tax Office. This research was conducted using qualitative qualifications. The method of data collection is done by survey method and questionnaire on accounting students' perceptions regarding the relationship between audit experience and motivation with tax audit performance. The sampling technique using purposive sampling technique. The technique of collecting data through primary data, and then the data are analyzed using descriptive qualitative analysis, and analysis of product renewal coefficients. Simultaneous research results, Perception of accounting students of PTS UMI said that there was a very low positive relationship with the value of conflict -0.101 in accounting students of PTS Unismuh Makassar said that there was a negative relationship with a comparison value of -0.101. In this research, the output target to be achieved is to produce a national journal, so that the output target can contribute to students or improve in developing insight knowledge in the field of tax accounting